PENGEMBANGAN MODEL-MODEL LATIHAN PUKULAN LOOP DRIVE FOREHAND TENIS MEJA DI PTM TRI DHARMA MALANG - Jotok Adam Harmono; Sri Purnami; Imam Hariadi (Jurnal Pendidikan Jasmani, 2015)
ABSTRACT: Hit forehand loop drive, the basic techniques of table tennis. This research aims to create a model of practice punch forehand loop drive in PTM Tri Dharma Malang. The method which researchers used refers to the development model of Borg and Gall. Data analysis technique which is being used is the qualitative and quantitative analysis in the form of a percentage. The trial results of small groups based on all product specifications is 90,54 % and testing a large group is 94,14%. So that the exercise model hit forehand loop drive to the beginner athlete of Tri Dharma Malang PTM can be used.ABSTRAK: Pukulan Loop drive Forehand ,merupakan teknik dasar dari tenis meja. Penelitian ini bertujuan membuat model latihan pukulan loop drive forehand tenis meja di PTM Tri Dharma. Peneliti menggunakan prosedur pengembangan (research and development) dari Borg and Gall.Teknik analisis data yang digunakan adalah analisis kuantitatif dan kualitatif berupa persentase. Hasil uji coba kelompok kecil adalah 90,54 % dan uji coba kelompok besar 94,14%. Sehingga model latihan pukulan loop drive forehand dapat digunakan di PTM Tri Dharma Malang.Kata kunci: model latihan, loop drive forehand, tenis meja